PROFIT SHARING AND BUYING-SELLING FINANCING: WHICH DETERMINES SUSTAINABILITY OF ISLAMIC BANKING DURING COVID-19 PANDEMIC? - Utomo, Sigit Prihanto; Afkar, Taudlikhul; Sugijanto, Sugijanto; Subakir, Subakir; Cahyani, Yasmine Dwi; Wati, Tarisya Maulidya (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Business activity of Islamic banks is to channel financing with the aim of making a profit. Profit-sharing financing is a characteristic of Islamic Banks that use mudharabah and musharakah contracts. In addition, it is also equipped with buying and selling financing using murabahah, istishna’, and ijarah contracts. Of course, during the Covid-19 pandemic, financial turmoil can have an impact on the ability to earn profits as a form of banking business sustainability. The purpose of this research is to conduct an analysis of the sustainability of Islamic banks during the Covid-19 pandemic through the distribution of profit-sharing financing and buying-selling financing so that the financing that will be known most strengthen the sustainability of Islamic banks in terms of the ability to earn profits. The population in this research is Islamic banks in Indonesia which are sampled with the Saturated sampling technique, so that over all 14 Islamic banks are used in research this. The data analysis technique used is multiple linear regression with the JAMOVI Data tool used 2019-2022 as a year to conduct an analysis of Islamic bank sustainability. Findings of this study show that the most dominant determination of the sustainability of Islamic banks during the Covid-19 pandemic is mudharabah financing